Prevalence of suicidal behaviour among nursing and midwifery college students in Ghana - Emmanuel Nii‐Boye Quarshie; Haziel Vera Cheataa‐Plange; Francis Annor; Winifred Asare‐Doku; Joshua King Safo Lartey (Wiley, 2019)
Abstract Aim To provide exploratory and descriptive evidence on the prevalence estimate and some demographic correlates of suicidal behaviour among nursing and midwifery college students in Ghana. Design We used a cross‐sectional survey design. Method An anonymous survey involving a randomly selected sample of 305 nursing and midwifery college students was conducted in March-May 2017. The Suicide Behavior Questionnaire‐Revised was used to assess suicidal behaviour (i.e., ideation, planning, threat and attempt) and suicidal behaviour risk. Results The lifetime prevalence of suicide ideations (15.4%; 95% confidence interval [CI] = 0.11-0.20), plans (6.6%; 95% CI = 0.04-0.10), attempts (2.3%; 95% CI = 0.01-0.05), threats (13.4%; 95% CI = 0.10-0.18) and 12‐month prevalence of ideations (21.3%; 95% CI = 0.17-0.26) are comparable to estimates found in both high‐income and low‐ and middle‐income countries. However, associations between the demographic variables studied and suicidal behaviour risk were not statistically significant.